ARCIMBOLDO on coiled coils. Issue 3 (5th April 2018) - Caballero, Iracema; Sammito, Massimo; Millán, Claudia; Lebedev, Andrey; Soler, Nicolas; Usón, Isabel
Abstract : The ARCIMBOLDO method of phasing through the location of small fragments combined with density modification and autotracing is particularly suited to helical structures, but coiled coils remain challenging. Features designed for solving coiled coils at resolutions of up to 3 Å were tested on a pool of 150 structures. Abstract : ARCIMBOLDO solves the phase problem by combining the location of small model fragments using Phaser with density modification and autotracing using SHELXE . Mainly helical structures constitute favourable cases, which can be solved using polyalanine helical fragments as search models. Nevertheless, the solution of coiled‐coil structures is often complicated by their anisotropic diffraction and apparent translational noncrystallographic symmetry. Long, straight helices have internal translational symmetry and their alignment in preferential directions gives rise to systematic overlap of Patterson vectors. This situation has to be differentiated from the translational symmetry relating different monomers. ARCIMBOLDO_LITE has been run on single workstations on a test pool of 150 coiled‐coil structures with 15–635 amino acids per asymmetric unit and with diffraction data resolutions of between 0.9 and 3.0 Å. The results have been used to identify and address specific issues when solving this class of structures using ARCIMBOLDO . Features from Phaser v.2.7 onwards are essential to correct anisotropy and produce translation solutions that will pass the packing filters. As the resolution becomes worse than 2.3 Å, the helix direction may be reversed in the placed fragments. Differentiation between true solutions and pseudo‐solutions, in which helix fragments were correctly positioned but in a reverse orientation, was found to be problematic at resolutions worse than 2.3 Å. Therefore, after every new fragment‐placement round, complete or sparse combinations of helices in alternative directions are generated and evaluated. The final solution is once again probed by helix reversal, refinement and extension. To conclude, density modification and SHELXE autotracing incorporating helical constraints is also exploited to extend the resolution limit in the case of coiled coils and to enhance the identification of correct solutions. This study resulted in a specialized mode within ARCIMBOLDO for the solution of coiled‐coil structures, which overrides the resolution limit and can be invoked from the command line (keywordcoiled_coil ) or ARCIMBOLDO_LITE task interface in CCP 4 i .